Trading Up to High Income : Turkey Country Economic Memorandum - World Bank (Washington, DC, 2014)
Turkish exporters substantially broadened market reach, exporting to 137 countries at present, up from 90 in 2000. Turkey's global market share rose substantially from 0.55 percent of global imports in 2002 to 0.82 percent in 2012. Turkey aims to become one of the ten largest economies in the world by 2023, with per-capita gross domestic product (GDP) rising to United States (U.S.) $25,000 and exports to U.S. 500 billion dollars. This report focuses on Turkey's competitiveness from the supply side, but it is important to note that ensuring a more balanced mix of financing for the required investment through measures to boost domestic savings is equally important if Turkey's progress is to be sustained. Achieving Turkey's export target is possible and it will likely require a larger global market share. The relatively low level of foreign direct investment (FDI) in Turkish manufacturing has been a constraint to export growth and quality improvements. Raising export growth to levels that help meet Turkey's development goals will require a policy agenda that targets sustained further improvements in Turkey's physical, human, and institutional capital. This report prioritizes broader policies that are fundamental for Turkey to export its way out of middle-income. Chief among these are policies that: (i) link the country further with international markets, including by helping bring larger inflows of FDI, particularly into the manufacturing sector; (ii) promote innovation, including by encouraging a large role for private companies in research and development (R and D); (iii) upgrade the skills both of the existing work force and new entrants; and (iv) improve access to finance, particularly long-term, with a view to unlock the potential of the dynamic small and medium enterprise (SME) sector.